Customer revisit intention towards casual dining restaurants in Klang valley, Malaysia - Lim, Wai Yin (2019)
The purpose of conducting this research project intends to investigate the factors like foodscape, service quality and restaurant environment that will impact on the customer satisfaction, in turn, customer revisit intention. Furthermore, to achieve the goal of this research project, research questions, and four hypotheses were formed and examined. I had distributed survey questionnaire to 300 respondents by using the judgment sampling technique, snowball sampling technique and convenient sampling technique. There are 70% sets of questionnaires were distributed through online such as the social media (Facebook) by using the convenience sampling technique. The other 30% were distributed physically. Through the use of Statistical Package for Social Science (SPSS), data collected through the survey questionnaires are able to be measured and analyzed. It followed by the Pilot Test, Reliability Test as well as the Multiple Regression Analysis, which are conducted to examine the significant relationship between the variables. The results acquired from the SPSS test are discussed and analyzed in the form of charts and tables in this paper. The major findings of this research project were discussed in order to understand the relationship between foodscape, service quality, restaurant environment and customer satisfaction. Moreover, in this research, the result shows that the all the independent variables have significant positive relationship with the customer revisit intention. This research provides a clearer overview for the food service industry, especially casual dining sector. Last but not least, the limitations of the study which include the limitation and delimitation associated with this research project were identified and implications for the further research were recommended.